Selection of running shoes by amateur runners: characterization and association with the self-reported history of injury (Fisioterapia e Pesquisa, 2022)
Running shoes are an essential elementfor sports practice. Evidence on the effect of the shoecharacteristics and prescription in running injuries arescarce. Thus, this study aimed to investigate runners'sprocess of choosing running shoes and to verify whetherthe variables related to running shoes and their selectionprocess are associated with the presence and recurrenceof injuries in the previous year. An observational study wasconducted with 254 runners who answered a self-reportedquestionnaire about demographics, sports practice, shoecharacteristics and selection criteria, and injuries in the last12 months. The chi-square test evaluated whether there wasa difference in the distribution of answers to each question.The logistic regression evaluated whether the variablesrelated to shoes and selection criteria predicted injury’spresence and recurrence in the previous year. The resultsshowed that most runners had specific shoes for sports